Environmental, Occupational Exposures to Benzene and Cancer: a Meta –analysis - Setiani, Onny (Jurnal Kesehatan Lingkungan Indonesia, 2005)
ABSTRACT Background: Many epidemiological studies have been able to address the relationships between benzene exposure in the environment  and  the level of risk. Incidence has risen in industrialized countries since the 1960s and is highly and rapidly fatal and represent the fifth leading cause of deaths from cancer  and 50%-100%  more  common in men than women. To identify, appraising and synthesizing  the risk of cancer from benzene exposure in environment or workplace,  a meta analysis is conducted. Method: Epidemiological studies were identified through a computerized Medline and search on follow up and case control studies.  The risk were identified as Standardized Mortality Ratios (SMRs), Standardized Incidence Ratios (SIRs), Relative Risk (RR) and Odd Ratio (OR).   Data extraction covered characteristic of the study (publication year, country, study type, case definition, sources of cases, reference population, follow up period, risk measures) and  risk estimates. The extracted data were checked for consistency and entered into a database and checked for correctness. Summary of  relative risk was calculated from log(RR) and log(upper and lower limit of 95% CI of log RR). SE and weight of all studies were estimated by fixed effect model. Results: The identified studies  were industrial-based (n=6), community-based (n=2),  and multicentre hospital-based study (n=2). RR of each study were also show benzene exposure was favour to risk of malignancy. This findings indicated workers who were exposed to benzene have risk to get malignancy 2 times higher than  person who were not exposed to benzene. The excess risk found for Benzene was based on 8 population that were exposed with benzene from oil or petroleum  industry. The risk of soft tissue carcinoma due to benzene exposure was highest  with RR=15,59 (95% CI= 1.74-139.3).  The lowest risk was  stomach carcinoma RR 2,51  (95% CI= 1,60-2,94) and hemopoetic malignancy in general with RR 2,63  (95% CI= 0,90-7,69). Conclusions:This meta-analysis suggest that environmental or occupational exposures of benzene may increase the risk of cancer,  with the highest case of soft tissue carcinoma and the lowest case of  stomach cancer. The excess may be pronounced in men who works in petroleum industry for more than 10 years and exposed to moderate and even level of benzene. Keywords: benzene, malignancy, industry, petroleum